DAMPAK REGULASI FINANCIAL TECHNOLOGY (FINTECH) TERHADAP RENTABILITAS PADA PERUSAHAAN PEMBIAYAAN YANG TERDAFTAR DI OTORITAS JASA KEUANGAN - Santoso, Ferry; Maya Saphira , Dinda (Jurnal Kewirausahaan Bukit Pengharapan, 2023)
The Objective of this study is to analyze the impact of Financial Technology (FinTech) regulation toward rentability of Funding Companies listed by Financial Services Authority. The Financial Services Authority (OJK) issued regulations regarding regulations for information technology-based money lending and borrowing services as stated in OJK Regulation Number 77/PJOK.01/2016. The research conducted different tests to analyze differences in rentability ratios of financing companies before and after the FinTech regulations The rentability ratios analyzed included ROA, ROE, NIM and BOPO. The population of this research is financing companies registered by the Financial Services Authority (OJK) using a purposive sampling technique. This research use paired sample T-Test to test hypothesis. The results of this research show that there is no significant difference in the ratio of Return On Assets, Return On Equity, and Net Interest Margin in finance companies before and after financial technology regulations. However, in the ratio of Operating Expenses and Operating Income there are significant differences between before and after financial technology regulations